(untitled) (ENTHYMEMA, 2019)
The article compares the representation of Asian sex workers in William T. Vollmann’s Butterfly Stories(1993) and Michel Houellebecq’s Platform(Plateforme, 2001). Both the novels are set in South-East Asia, and both involve an apologetic and romanticised description of the sex trade. By comparing the two novels, I argue that both authors’ treatments of the sex industry develop a critique of Western Orientalism, and at the same time sympathy for and complicity with the colonial power dynamics that regulate the relationships between Asian countries and the West.